Engineering for climatic change proceedings of the symposium on engineering in the uncertainty of climatic change, organized by the Institution of Civil Engineers and held in London on 28 October 1992 - White, Roger, 1935- (Thomas Telford, 1993)
Including the keynote paper by Sir Crispin Tickell, an international authority on the implications of climate change, the scene is set by three eminent speakers in the fields of meteorology, hydrology and oceanography, and the scenario they present provides a backcloth for the papers that follow. These papers show that the civil engineering profession is taking the question of climate change very seriously.